Fostering Joyful Engagement: Integrating Positive Psychology Activities in English for Specific Purposes (ESP) Classrooms for Non-English Majors - Kurniawan, Nova Adi; Ridhwan, M (Yayasan pendidikan dzurriyatul Quran, 2025)
Traditional ESP instruction for non-English majors often neglects affective factors, exacerbating anxiety and disengagement in contexts like Indonesian Islamic higher education. This study addresses this gap by integrating Positive Psychology (PP) activities into an ESP course for Sharia Economics students. An explanatory sequential mixed-methods design was employed with all 17 students in the cohort. Quantitative data (pre-/post-questionnaires, language tests, structured observations) measured changes in joyful engagement and discipline-specific language skills. Qualitative data (interviews, reflective journals) explored experiential insights. Analysis used paired t-tests, correlations, and thematic analysis. PP activities generated statistically significant increases in joyful engagement – AEQ Enjoyment Δ = +1.37; observed enthusiasm +338%) and language acquisition (vocabulary +13.53%, text comprehension +14.12%, presentation skills +15.29%; all p < 0.001. A strong correlation emerged between joy and learning gains (r = 0.72). Qualitatively, students highlighted reduced anxiety, enhanced relevance through Islamic economic scenarios, such as zakat negotiations, and cultural-religious synergy - gratitude as shukr. Joy-centered pedagogy, grounded in PP principles and contextualized within Islamic values, proves highly effective in transforming ESP learning for non-English majors. It reduces affective barriers, fosters meaningful engagement, and accelerates discipline-specific language proficiency. This study provides a replicable model for affective ESP pedagogies in religious Indonesian higher education, prioritizing both academic rigor and holistic development.